HAND AND KNEE POSITION ON THE PROGRESS OF LABOR IN THE FIRST ACTIVE PHASE LABOR AT PMB SOESI HERAWATI KEPANJEN, MALANG DISTRICT - Dini Ria Oktaavia; Endah Sri Wulandari; Faiqotul Muktamaroh (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
Background: Abnormal labor patterns can occur during the active phase of labor, such as when cervical dilation takes longer than 6 hours, leading to prolonged labor, maternal and neonatal emergencies, or the need for a cesarean delivery. The hand-and-knee position can help rotate the fetus from a less ideal position (occipito-posterior) to a more favorable position (anterior), facilitating the baby's descent and speeding up cervical dilation.Method: This study was conducted on 20 women in active labor at PMB Soesi Herawati Kepanjen. It compared two groups: those who used the hand-and-knee position and those who did not. A quasi-experimental design was used, with data collected using observation sheets and partographs, and analyzed with the Fisher's exact test in SPSS 25.0.Result: The results showed a significant effect of the hand-and-knee position on labor progress during the active phase, with a p-value of 0.011 (α < 0.05). The hand-and-knee position helps create more space in the pelvic area, allowing the baby to move into an optimal position and speeding up cervical dilation.Conclusion: The research concludes that the hand-and-knee position can help the fetus rotate into an ideal position, aiding cervical effacement and the descent of the fetal head, thus speeding up the active phase of labor. Midwives are encouraged to promote this position to mothers in labor, as it can facilitate cervical dilation and help the fetus descend deeper into the pelvis